Executive Committee Minutes 2005-02-03 - Academic Senate:::::::::
Faculty Eligible for Emeritus Status, Faculty Governance Release Time for '05 – '06, Excellence in Teaching Committee, SB1212 implementation, CSU and SSU Data Summary: SFR & Average Class Size